2007
DOI: 10.1002/gepi.20294
|View full text |Cite
|
Sign up to set email alerts
|

Confronting complexity in late‐onset Alzheimer disease: application of two‐stage analysis approach addressing heterogeneity and epistasis

Abstract: Common diseases with a genetic basis are likely to have a very complex etiology, in which the mapping between genotype and phenotype is far from straightforward. A new comprehensive statistical and computational strategy for identifying the missing link between genotype and phenotype has been proposed, which emphasizes the need to address heterogeneity in the first stage of any analysis and gene-gene interactions in the second stage. We applied this two-stage analysis strategy to late-onset Alzheimer disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…A common Alu (indel) insertion(I)/deletion(D) polymorphism (rs 1799752) in intron 16 of the ACE gene was reported to be associated with sporadic AD, the greatest risk being associated with homozygosity of the I allele (Kehoe et al, 1999 ). This was confirmed in several meta-analyses (Narain et al, 2000 ; Kehoe et al, 2003 ; Elkins et al, 2004 ; Lehmann et al, 2005 ) and was supported to some extent by some of the earlier whole-genome association studies (Li et al, 2008 ; Thornton-Wells et al, 2008 ) although a number of more recent and larger studies have failed to find any association. In the original studies, homozygosity of the D and I alleles was associated with the highest and lowest ACE protein level in the periphery, respectively, (Rigat et al, 1990 ) although this association only partly explains the total variance of ACE in the periphery (Terao et al, 2013 ).…”
Section: The Renin-angiotensin System In Alzheimer's Diseasementioning
confidence: 73%
“…A common Alu (indel) insertion(I)/deletion(D) polymorphism (rs 1799752) in intron 16 of the ACE gene was reported to be associated with sporadic AD, the greatest risk being associated with homozygosity of the I allele (Kehoe et al, 1999 ). This was confirmed in several meta-analyses (Narain et al, 2000 ; Kehoe et al, 2003 ; Elkins et al, 2004 ; Lehmann et al, 2005 ) and was supported to some extent by some of the earlier whole-genome association studies (Li et al, 2008 ; Thornton-Wells et al, 2008 ) although a number of more recent and larger studies have failed to find any association. In the original studies, homozygosity of the D and I alleles was associated with the highest and lowest ACE protein level in the periphery, respectively, (Rigat et al, 1990 ) although this association only partly explains the total variance of ACE in the periphery (Terao et al, 2013 ).…”
Section: The Renin-angiotensin System In Alzheimer's Diseasementioning
confidence: 73%
“…In a two-stage analysis assessing for heterogeneity and gene-gene interactions in 22 candidate genes, LRRTM3 SNPs were identified to be the most influential in determining clusters for AD risk [15]. Furthermore in this study, LRRTM3 SNP multilocus genotypes (MLGs) were shown to have statistical interactions with PLAU , previously implicated in AD risk and Aβ levels [16], as well as CDC2 and ACE in conferring AD risk.…”
Section: Introductionmentioning
confidence: 68%
“…Indeed, two other studies utilized the MLG approach with LRRTM3 SNPs and showed association with AD risk. One study identified 5 LRRTM3 SNPs, the MLGs of which formed three clusters, wherein variants of PLAU , CDC2 and ACE showed significant AD risk association [15]. Another study identified two and three locus genotypes with SNPs in LRRTM3 , ACE and A2M that associate with AD risk [17].…”
Section: Discussionmentioning
confidence: 99%
“…A large region of chromosome 10, including the region encoding LRRTM3, has received attention in relation to the development of late-onset AD. Investigations of SNPs potentially related to late-onset AD, as well as other statistical and genetic studies, have observed SNPs in LRRTM3 as well as CCTNNA3 (the α-Catenin-encoding gene in which LRRTM3 is nested in an intron) and identifi ed LRRTM3 as a potential late-onset AD candidate gene (Reitz et al 2012 ;Liang et al 2007 ;Thornton-Wells et al 2008 ;Edwards et al 2009 ).…”
Section: Diseasesmentioning
confidence: 98%